2017
DOI: 10.1021/acs.jpcc.7b07136
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Polarization Measurements to Probe Alignment of a Bithiophene Dye in One-Dimensional Channels of Self-Assembled Phenylethynylene Bis-Urea Macrocycle Crystals

Abstract: This thesis describes the use of polarized fluorescence microscopy to directly probe guest molecule orientation in bis-urea macrocycle crystals. These macrocycles assemble to afford one-dimensional (1D) microchannels ∼9 Å in diameter that have previously been shown to exhibit normal Fickian diffusion and induce selective reactivity among the confined guest molecules. In the present work, we take advantage of the quasi-1D morphology of fiber-like microcrystals with the extended dimension corresponding to the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…The fabrication of these hierarchically organized photoactive materials and their use as artificial antenna systems, pioneered by the Calzaferri group,,,,,, has been thoroughly investigated and the acquired knowledge played a seminal role, for example, in extending their scope to biomedical uses . Also importantly, dye‐zeolite L hybrids stimulated the quest of new host matrices for luminescent supramolecular systems: not only zeolite frameworks of diverse shape and composition,, but also mesoporous silicas/organosilicas,,,, 1D macrocycle channels,, and MOFs ,,…”
Section: Organization Of Complex Species In 1dmentioning
confidence: 99%
“…The fabrication of these hierarchically organized photoactive materials and their use as artificial antenna systems, pioneered by the Calzaferri group,,,,,, has been thoroughly investigated and the acquired knowledge played a seminal role, for example, in extending their scope to biomedical uses . Also importantly, dye‐zeolite L hybrids stimulated the quest of new host matrices for luminescent supramolecular systems: not only zeolite frameworks of diverse shape and composition,, but also mesoporous silicas/organosilicas,,,, 1D macrocycle channels,, and MOFs ,,…”
Section: Organization Of Complex Species In 1dmentioning
confidence: 99%
“…The supramolecular assembly of chromophores provides an alternative approach to modulate photophysics and afford functional hierarchical materials. Self-assembly often leads to dramatic changes in photophysics, formation of porous materials, , and can result in the emergence of new properties such as persistent radical formation. , Recently, our group reported that self-assembled benzophenones 2 – 4 (Figure ) exhibit persistent radical formation upon irradiation with UV light when in the solid-state but show no radicals in solution . Here, we examine how solid-state assembly of two benzophenone (BP) bis -urea macrocycles and two methylene-urea tethered dibenzophenones 1–4 influences the rate of radical formation, maximum quantity of radicals, and radical regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Specific to photoluminescent materials with structural anisotropy, besides the nanostructured effect, the linear polarization degree of the PL is essentially determined by the optical transition (electric) dipole moments in the crystals. , In the past decades, the polarized PL emissions have been demonstrated in the anisotropic packing of chromophores in the polymer fibers, , metal organic frameworks and organometallic crystals, but only displayed low polarization degree less than 0.9. This is rooted in the disordered distribution nature of the transition dipole moments in these reported PL crystalline materials, which allows for unidirectional electromagnetic oscillations (Figure a).…”
mentioning
confidence: 99%
“…However, it is very challenging to enforce uniform orientation of all transition dipole moments, which can be significantly affected by the steric hindrance of molecular packing, molecular vibrations, and material defects. For instance, even in one-dimensional photoluminescent polymers where the structure anisotropy is extremely high as a result of dimensionality, the polarization degree of the PL is still lower than 0.9 because of the influence of depolarization interaction from the dielectric surroundings. …”
mentioning
confidence: 99%